Religion und Geschlecht - Heller, Birgit (De Gruyter Studium, 2024)
Religious traditions, symbols, and practices are shaped by gender gender roles, stereotypes, and ideals have religious underpinnings. Studying gender in religious studies means taking the category of gender into account when collecting, describing, and analyzing data pertaining to religion. It also means uncovering the normativity of entanglements between religion and gender as well as making opposing trends visible